2006
DOI: 10.1096/fj.05-4870fje
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome blockade exerts an antifibrotic activity by coordinately down‐regulating type I collagen and tissue inhibitor of metalloproteinase‐1 and up‐regulating metalloproteinase‐1 production in human dermal fibroblasts

Abstract: Tissue fibrosis results when dysregulation of extracellular matrix (ECM) turnover favors deposition of collagen and other ECM proteins over degradation. Fibrosis may then lead to organ dysfunction and pathology as observed in systemic sclerosis (SSc). In the present study, we investigated the antifibrotic properties of proteasome blockade. A dose- and time-dependent reduction in type-I collagen and tissue inhibitor of metalloproteinase-1 (TIMP-1) production was observed in normal fibroblasts exposed to proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 52 publications
13
58
0
Order By: Relevance
“…In contrast to bafilomycin A 1 , we observed that the inhibition of the proteasome by treatment with MG132 repressed the expression of Col-I ␣1 mRNA in MMC. Similar effect of MG132 has been previously reported in human dermal fibroblasts (43) and rat cardiac fibroblasts (44).…”
Section: Disruption Of Autophagic Activity Suppresses Intracellular Dsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast to bafilomycin A 1 , we observed that the inhibition of the proteasome by treatment with MG132 repressed the expression of Col-I ␣1 mRNA in MMC. Similar effect of MG132 has been previously reported in human dermal fibroblasts (43) and rat cardiac fibroblasts (44).…”
Section: Disruption Of Autophagic Activity Suppresses Intracellular Dsupporting
confidence: 88%
“…This negative regulatory effect of MG132, in fact, has been previously shown in human dermal fibroblasts (43) and rat cardiac fibroblasts (44). However the precise mechanism by which proteasome inhibitor MG132 represses Col-I ␣1 mRNA expression remains to be determined.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…To date, steroids are the most effective and utilized treatment, but new immune-modulatory drugs have been experimented to improve muscle repair by reducing inflammation and fibrosis of DMD animal models as anticytokines (anti-TNFα), 30 IL-6r blockade, 31 TGF-β blocker (suramin and pirfenidone) 32,33 and, more recently, Treg expansion. 13 Several evidences suggested that the proteasome is directly involved in the pathophysiology of organ fibrosis: inhibition of the proteasome could block TGF-β1 induced gene expression in primary human lung fibroblasts from healthy individuals and patients with IPF 34,35 and could reduce lung fibrosis in some animal models. 36,37 Indirectly, fibrosis is augmented by inflammatory pathogenesis that is also influenced by i-proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned media from equal cell numbers were concentrated fivefold and analysed for total collagen (types I-V) using a Sircol soluble collagen assay kit as described (Biocolor Ltd) (Fineschi et al, 2006). Collagen was measured by reference to a type-I collagen standard curve.…”
Section: Collagen Assaymentioning
confidence: 99%